Capacitive Deionization for Selective Extraction of Lithium from Aqueous Solutions - Bryjak, M.; Siekierka, A.; Kujawski, J.; Smolinska-Kempisty, K.; Kujawski, W. (Journal of Membrane and Separation Technology, 2015)
The paper deals with extraction of lithium by means of two capacitive deionization systems: one composed of lithium selective electrode and second with electrode wrapped with Li-selective membrane. In the case of the first system, hybrid electrodes where obtained by mixing λ-MnO2sorbent with activated carbon .The best Li-capacity was determined for electrode with 20 wt.-% of manganese oxide. For larger amounts of λ-MnO2 the electrode capacity decreased significantly. The second system was composed of carbon electrodes wrapped with ion-exchange membranes. The lithium selective membranes were synthesized by plasma induced interpolymerization of (meth)acrylic monomersinpores of Celgard 2400 support. Two functional monomers, poly(di(ethylene glycol)methyl ether methacrylate) and poly(glycidylmethacylate modified with hydroxymethyl-12-crown-4) were copolymerized with acrylic acid. It was found that the extraction of lithium chloride was the best for membrane caring copolymers of acrylic acid and glycidyl methacrylate modified with crown ether, andit was better than for membranes with sole poly(acrylic acid).